If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + -2 + -3b = 16 Reorder the terms: -2 + -3b + 6p = 16 Solving -2 + -3b + 6p = 16 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2' to each side of the equation. -2 + -3b + 2 + 6p = 16 + 2 Reorder the terms: -2 + 2 + -3b + 6p = 16 + 2 Combine like terms: -2 + 2 = 0 0 + -3b + 6p = 16 + 2 -3b + 6p = 16 + 2 Combine like terms: 16 + 2 = 18 -3b + 6p = 18 Add '-6p' to each side of the equation. -3b + 6p + -6p = 18 + -6p Combine like terms: 6p + -6p = 0 -3b + 0 = 18 + -6p -3b = 18 + -6p Divide each side by '-3'. b = -6 + 2p Simplifying b = -6 + 2p
| 14m^2+2m=0 | | (5a+10)+(3a+10)=180 | | -h/6+1=-1 | | 2[X+2]-X=3[X+1]+9 | | 3b-4+b=8 | | 17a=3a+7 | | -2(b+4)= | | 3x^2+6=7x | | 4x-9=3.5-9 | | -4.6x=18.4 | | 3(4x+5)=17 | | k/3+6=9 | | 147-2x=25x+24 | | 5x*3x= | | 3[2+W]-W=4+2[W+1] | | (5x)(3x)= | | 12=5r+8 | | x/3=15/8/23/4 | | (4x+36)+(96-x)=180 | | 6x-9= | | 1.1x-15=-35.9 | | -3y-7=23 | | r-4+6r=19-3x | | (4x-2)(x^2-4x+5)= | | 2y^2-5y+3= | | 4(2x-1)=34 | | -7z+7+5=-3z+12 | | 16b-12b= | | 2(4-3x)=4x-2 | | 18-5x=10+3x | | 25w^2+40w+16= | | 7=9a-2a |